Multimodal versus Conventional Approach for Postoperative Pain Relief in Oral Cancer Patients - Gunjan (J Clin Diagn Res, 2016)
INTRODUCTION: Multimodal analgesia includes regional anaesthesia in the form of nerve block may improve recovery along with optimal rehabilitation and early resumption of day-to-day activity following major surgery. Conventional general anaesthesia consists of premedication, induction, intubation and maintenance. AIM: The aim of the study is to compare the multimodal versus conventional approach in oral cancer surgery. MATERIALS AND METHODS: The patients were randomly allocated into three groups, 30 patients in each group using the computer generated random table to one of the following groups: Group A: Fentanyl 1 μg/kg, Group B: Fentanyl 1 μg/kg + bupivacaine local infiltration, Group C: Fentanyl 1 μg/kg + bupivacaine local infiltration + Dexemedetomidine infusion (Loading 0.5 μg/kg, Maintenance 0.2μg/kg/hr). RESULTS: No significant (p>0.05) difference was found in mean arterial pressure and heart rate at different time intervals among the groups. The VAS was lower in Group C than Group B and A. The ramsay sedation scale was higher in Group C than Group B and A. The rescue analgesic for 24 hour was lower in Group C than Group B and A. The time of first time analgesia requirement was significantly (p=0.001) higher in Group C than Group B and A. The rescue analgesic was significantly (p=0.001) lower in Group C (39.29±19.67) than Group B (68.33±18.49) and A (160.83±35.16). CONCLUSION: Multimodal analgesia has beneficial haemodynamic effects during oral cancer surgery with reliable postoperative analgesia and sedation and less postoperative complication. Dose of drugs used in our study is not associated with any major adverse effect.